The Impact of Product Innovation and Digital Capabilities on the International Competitiveness of Indonesian Culinary SMEs - Rikardus Kurnia Lango; Sudarmiatin Sudarmiatin; Heri Pratikto (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
The international competitiveness of Indonesian fashion SMEs still faces challenges, despite the sector having a large business base, strong export opportunities, and increasingly widespread access to digital technology. In this context, product innovation and digital capabilities are viewed as strategic resources that can strengthen SMEs’ ability to adapt and compete in broader markets. This study aims to analyse the influence of product innovation and digital capabilities on the international competitiveness of Indonesian fashion SMEs. The research employs an explanatory quantitative approach with a cross-sectional survey design. The sample consists of 200 owners or key managers of SMEs in East Java, selected via purposive sampling. Data were collected using a structured questionnaire and analysed using SEM-PLS. The results indicate that product innovation and digital capabilities have a positive and significant effect on international competitiveness, with digital capabilities acting as the dominant predictor. The implication is that efforts to strengthen the international competitiveness of fashion SMEs should be directed towards the integration of market-based innovation and strategic digital transformation.